2022
DOI: 10.33086/jhcs.v2i3.3142
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Hypertension Preventetion Program Through Hypertension Exercise for the Elderly at Wisma Cempaka Upt PSTW Puger Jember Regency

Abstract: Hypertension is increased blood pressure in the arteries continuously over a period, where the symptoms of hypertension are very diverse in each individual. Hypertension is a systolic and diastolic pressure of more than 160mmHg and 90mmHg, which is also common in the elderly. Objective: This study aims to determine the impact of providing health education related to hypertension and anti-hypertensive exercise on blood pressure in the elderly at Wisma Cempaka UPT PSTW Jember. This research used a quasi-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study by Pescatello, (2015), recommends that exercise be performed for 30-60 minutes every day continuously, with a total duration of 150 minutes per week. Supported by a study by Pratiwi, (2023), which found that hypertensive exercises have been proven to lower blood pressure quickly in hypertensive patients undergoing pharmacological treatment without engaging in exercise. Exercise could effectively control hypertension because the activity stimulates an increase in the strength of the heart's pump and promotes vasodilation of blood vessels, ensuring smooth blood flow.…”
Section: Hypertension Exercises Programmentioning
confidence: 99%
“…A study by Pescatello, (2015), recommends that exercise be performed for 30-60 minutes every day continuously, with a total duration of 150 minutes per week. Supported by a study by Pratiwi, (2023), which found that hypertensive exercises have been proven to lower blood pressure quickly in hypertensive patients undergoing pharmacological treatment without engaging in exercise. Exercise could effectively control hypertension because the activity stimulates an increase in the strength of the heart's pump and promotes vasodilation of blood vessels, ensuring smooth blood flow.…”
Section: Hypertension Exercises Programmentioning
confidence: 99%